Development and characterization of WE43/nano-TiC surface composite by friction stir processing technique. (March 2020) - Singla, Shivali; Kang, Amardeep Singh; Sidhu, TS
In present research work, an attempt has been made on the development of titanium carbide–reinforced magnesium-based surface composites through friction stir processing technique. Particularly, attempt has been made to observe the influence of input processing conditions, namely tools-pin geometry, travel speed, and rotational speed for the mechanical importance (surface hardness and elastic modulus) of the developed composites. Further, the, incurred modifications in the metallurgical characteristics and corrosion behaviour of the developed composites have also been analysed through microscopic and scanning electron microscopy, and immersion fluid test, respectively. It has been found that the quality characteristics of the composites have been greatly influenced by the selected range of input variables. As noticed, the grain size of the magnesium alloy has been significantly reduced from 22.42 to 6.6 µm. Furthermore, the maximum level of the micro-hardness (180 HV0.3 ) of the processed composite with square-shaped tool-pin geometry. Moreover, the degradation rate of the processed composite is found to be 45% lesser than the unprocessed magnesium alloy.